Heart Team: Joint Position of the Swiss Society of Cardiology and the Swiss Society of Cardiac Surgery - Pedrazzini, Giovanni B.; Ferrari, Enrico; Zellweger, Michael; Genoni, Michele (The Thoracic and Cardiovascular Surgeon, 2017)
The Swiss Society of Cardiology (SSC) and the Swiss Society of Cardiac and Thoracic Vascular Surgery (SSCTVS) have formulated their mutual intent of a close, patient-oriented, and expertise-based collaboration in the Heart Team Paper. The interdisciplinary dialogue between the SSC and SSCTVS reflects an attitude in decision making, which guarantees the best possible therapy for the individual patient. At the same time, it is a cornerstone of optimized process quality, placing individual interests into the background.Evaluation of the correct indication for a treatment is indeed very challenging and almost impossible to verify retrospectively. Quality in this very important health policy process can therefore only be assured by the use of mutually recognized indications, agreed upon by all involved physicians and medical specialties, whereby the capacity of those involved in the process is not important but rather their competence.These two medical societies recognize their responsibility and have incorporated international guidelines as well as specified regulations for Switzerland. Former competitors now form an integrative consulting team able to deliver a comprehensive evaluation for patients. Naturally, implementation rests with the individual caregiver. The Heart Team Paperof the SGK and SGHC, has defined guide boards within which the involved specialists maintain sufficient room to maneuver, and patients have certainty of receiving the best possible therapy they require.
Keywords: heart team; coronary artery disease; transcatheter aortic valve replacement